Navigating severe chronic cancer-related fatigue: an interpretative phenomenological analysis. Issue 4 (3rd April 2023) - Bootsma, Tom I.; Schellekens, Melanie P. J.; van Woezik, Rosalie A. M.; van der Lee, Marije L.; Slatman, Jenny
Abstract: Objective: This article presents a phenomenological study on the embodied experiences of patients with Chronic Cancer-Related Fatigue (CCRF), aiming to better understand this complex phenomenon. Design: Data collection consisted of individual interviews with 25 participants who suffered from severe CCRF for at least three months after cancer treatment was finished. Main outcome measures: Against the theoretical background of philosophical phenomenology, we explored embodied experiences, incorporated temporal and spatial aspects of living with CCRF. We applied interpretative phenomenological analysis (IPA) to analyze the transcripts of the interviews. Results: Using IPA, we identified four themes on how chronic fatigue is experienced post-cancer: (1) Worn out; (2) Diminishment of one's 'I can'; (3) Invisibility; and (4) Regaining one's 'I can'. Conclusion: For clinical practice, these results imply that professionals could focus more on the role of the body and limitations of one's 'I can' when treating CCRF. By studying these embodied CCRF experiences in individual patients, future research could help personalize and optimize treatment.